PEMETAAN COMPETENCY GAP LULUSAN PENDIDIKAN TEKNIK DALAM MENGHADAPI TUNTUTAN INDUSTRI ERA SOCIETY 5.0 - Andi Maga Umara; Hafid Rahmandan; Mohamad Riyandi Badu (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
The gap between the competencies of education-based vocational graduates and industry needs remains a concern, particularly because graduates are often perceived as less competitive than diploma (D3/D4) or pure Mechanical Engineering graduates. This study aims to map the competency gap of Mechanical Engineering Education graduates against industry needs in the Society 5.0 era, while also examining its relationship with study program curriculum coverage. This study used a quantitative-dominant mixed-methods design, involving total sampling of one representative respondent from each of 10 companies that had previously employed graduates, as well as 53 alumni of the Mechanical Engineering Education study program, complemented by industry interviews and curriculum document analysis. Data were analyzed using a gap score (the difference between industry importance level and alumni mastery level), the Mann-Whitney U test, Importance-Performance Analysis (IPA), and triangulation with the coverage status of competencies in the Graduate Learning Outcomes (CPL). The results show that the competency gap is dominated by soft skills (mean gap 0.45) and Society 5.0 technological competencies, particularly basic understanding of the Internet of Things (gap=1.06; p<.001), while basic engineering hard skills show a small gap (mean gap 0.02) and even a negative gap on several indicators. Competencies that are only implicitly covered in the CPL/CPMK show an average gap nearly four times larger than those explicitly covered. This finding is confirmed by industry interview results that highlight the gap between theoretical knowledge and real practical experience. The study concludes that strengthening graduate competencies should be directed toward formulating more explicit learning outcomes, accompanied by the implementation of project-based learning and practical experiences that involve industry more intensively. ABSTRAK Kesenjangan antara kompetensi lulusan pendidikan vokasi berbasis kependidikan dengan kebutuhan industri masih menjadi persoalan, terutama karena lulusan sering dipersepsikan kurang kompetitif dibanding lulusan D3/D4 atau Teknik Mesin murni. Penelitian ini bertujuan memetakan kesenjangan kompetensi (competency gap) lulusan Pendidikan Teknik Mesin terhadap kebutuhan industri pada era Society 5.0, sekaligus menelusuri keterkaitannya dengan cakupan kurikulum program studi. Penelitian ini menggunakan desain mixed-methods dengan dominasi kuantitatif (quantitative dominant), melibatkan total sampling terhadap satu responden perwakilan dari masing-masing 10 perusahaan yang pernah menerima lulusan, serta 53 alumni Program Studi Pendidikan Teknik Mesin, dilengkapi wawancara industri dan analisis dokumen kurikulum. Data dianalisis menggunakan gap score (selisih tingkat kepentingan industri dan tingkat penguasaan alumni), uji Mann-Whitney U, Importance-Performance Analysis (IPA), serta triangulasi dengan status cakupan kompetensi dalam Capaian Pembelajaran Lulusan (CPL). Hasil penelitian menunjukkan kesenjangan kompetensi didominasi oleh aspek soft skills (gap rata-rata 0,45) dan kompetensi teknologi Society 5.0, khususnya pemahaman dasar Internet of Things (gap=1,06; p<0,001), sementara hard skills dasar kerekayasaan justru memiliki gap yang kecil (gap rata-rata 0,02) bahkan negatif pada beberapa indikator. Kompetensi yang hanya tercakup implisit dalam CPL/CPMK memiliki gap hampir empat kali lebih besar dibanding yang tercakup eksplisit. Temuan ini dikonfirmasi oleh hasil wawancara industri yang menyoroti kesenjangan antara pengetahuan teoritis dan pengalaman praktik nyata. Penelitian ini menyimpulkan bahwa penguatan kompetensi lulusan perlu diarahkan pada perumusan capaian pembelajaran yang lebih eksplisit, disertai implementasi pembelajaran berbasis proyek dan pengalaman praktik yang melibatkan industri secara lebih intensif.